2013
DOI: 10.1136/bjsports-2013-092389
|View full text |Cite|
|
Sign up to set email alerts
|

Is there a relationship between subacromial impingement syndrome and scapular orientation? A systematic review

Abstract: The underlying aetiology of SIS is still debated. The results of this review demonstrated a lack of consistency of study methodologies and results. Currently, there is insufficient evidence to support a clinical belief that the scapula adopts a common and consistent posture in SIS. This may reflect the complex, multifactorial nature of the syndrome. Additionally, it may be due to the methodological variations and shortfalls in the available research. It also raises the possibility that deviation from a 'normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 54 publications
3
66
0
7
Order By: Relevance
“…Along with several basic studies, there has been particular interest in scapular kinematics during elevation of the arms. 10,11) In general, during arm elevation, the scapula rotates in three dimensions: upward rotation, posterior tilt, and external rotation with respect to the thorax. 12,13) Recent studies using electromagnetic sensor-based motion analysis devices have reported that the scapular kinematics of impingement syndrome patients (excluding rotator cuff tears) involve a significant decrease in motion compared to that of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Along with several basic studies, there has been particular interest in scapular kinematics during elevation of the arms. 10,11) In general, during arm elevation, the scapula rotates in three dimensions: upward rotation, posterior tilt, and external rotation with respect to the thorax. 12,13) Recent studies using electromagnetic sensor-based motion analysis devices have reported that the scapular kinematics of impingement syndrome patients (excluding rotator cuff tears) involve a significant decrease in motion compared to that of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluate the effect of loading on scapular movement, as other studies have suggested that differences in kinematics are clearer in the presence of loading. 10,35,36 4. Investigate the relationship between shoulder pathology, age, years since injury, and body mass index (BMI) and scapular positioning.…”
Section: Dynamic Three-dimensional Ultrasound To Evaluate Scapular Momentioning
confidence: 99%
“…7,8 Ratcliffe et al, conducted a systematic review and reported insufficient evidence to support the role of aberrant posture in the pathogenesis of SAIS potentially due to the complex and multifactorial nature of SAIS and lack of consistency between study methodologies. 10 Considering contradictory reports, more research is needed for the identification of aberrant postural adaptations in SAIS patients in order to facilitate the implementation of assessment-driven targeted interventions. Hence, the purpose of this study was to compare several postural variables between the SAIS patients and asymptomatic healthy controls.…”
Section: Pbackgroundmentioning
confidence: 99%